Urgensi Pendidikan Kebencanaan Kepada Masyarakat - Nur Hamid (Equilibrium: Jurnal Pendidikan, 2020)
Disaster is going to happen whenever and wherever people are. Not every area is equipped with early warning system towards disasters, alleviating people panic to become extremely serious issues that need solution. This publication aims to highlight the significance of disaster education for society so they can act accordingly when disaster strikes. Method used on this study was literature study method which is a method conducting by reading, scrutinizing, acknowledging, outlining, and analyzing literatures from books, journals, and secondary data related to disaster education. The study revealed that up to this time, there have been not a reliable method to employ for disaster education either in formal and non-formal education yet, even in informal one. However, in general, disaster education that can represent and be adopted as an alternative is in forms of disaster training, activities to promote people awareness, introduction of the topic through work publication, workshop or seminar, simulation, exhibition, and other activities based on local wisdom.